2013
DOI: 10.3941/jrcr.v7i8.1342
|View full text |Cite
|
Sign up to set email alerts
|

Primary Renal Lymphoma Mimicking a Subcapsular Hematoma: A Rare Case Report

Abstract: Primary renal lymphoma (PRL) is a rare entity with a history of controversy regarding its existence. Lymphomatous involvement of the kidney is more commonly seen secondarily to spread from an adjacent lymphomatous mass, rather than arising primarily from the kidney. PRL can mimic other renal lesions such as renal cell carcinoma, renal abscess, and metastasis; therefore, an early diagnosis is crucial to guide treatment and properly assess prognosis. We present a rare case of a 77 year-old male who presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Earlier reports have shown that cases other than the indolent type of marginal zone lymphoma have a poor prognosis with a median survival of less than one year (4). Such cases behave in an aggressive manner and often disseminate to the lymph nodes (21) or other organs including the central nervous system (11,20,26) Until now, a limited number of cases has been published in which the lymphoma cells were proven to have been restricted to the kidney based on the PET analysis (11,25,31). If PET/CT had been used as a routine investigation, previously diagnosed PRL cases may have been revised to disseminated or advanced stages of lymphomas and the prognosis of the limited stage should be equivocal to those of other common types of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports have shown that cases other than the indolent type of marginal zone lymphoma have a poor prognosis with a median survival of less than one year (4). Such cases behave in an aggressive manner and often disseminate to the lymph nodes (21) or other organs including the central nervous system (11,20,26) Until now, a limited number of cases has been published in which the lymphoma cells were proven to have been restricted to the kidney based on the PET analysis (11,25,31). If PET/CT had been used as a routine investigation, previously diagnosed PRL cases may have been revised to disseminated or advanced stages of lymphomas and the prognosis of the limited stage should be equivocal to those of other common types of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cases of renal lymphoma are clinically asymptomatic and incidentally founded at imaging. Immunocompromised patients are at significantly higher risk for developing lymphoma [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…On CT it features as a soft-tissue homogenous mass, slightly hyperdense compared to the adjacent unenhanced renal parenchyma [ 4 ]. On MRI, lymphoma demonstrates hypointense signal on T1-weighted images (WI) and is slightly hypointense or isointense relative to normal renal cortex on T2-WI.…”
Section: Discussionmentioning
confidence: 99%
“…We thoroughly reviewed all 54 cases of PRL reported in the literature since 2002 (Table 1). 4,749 DLBCL was found to be the most common pathological type, and more male than female patients (64.8%) were reported. Additionally, PRL was generally located in the bilateral kidneys in younger patients (<30 years old) and in a unilateral kidney in older patients, indicating that the site of PRL is age-related.…”
Section: Discussionmentioning
confidence: 99%